Wanita Karir, Studi Kritis Perspektif Maqashid Syariah - Ahmad Syafii Rahman; Siti Aisyah; Moh Shofiyul Huda MF; Rubini Rubini; Rahma Pramudya Nawang Sari (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
Islam exists to liberate mankind from unequal social conditions. Islam rejects all forms of tyranny, exploitation, domination, and hegemony in various aspects of life: economy, politics, culture, gender and others. Basically Islam never forbids women who want to work (career). This study tries to analyze the position of career women in the perspective of Maqashid sharia. This research was conducted using a conceptual approach, namely the Maqashid Shari'ah concept. The results of this study indicate that there are five objectives of maqashid ash-shari'ah, namely to protect or ensure the continuity of one's faith (hifdz ad-din), their lives (hifdz nafs), their minds (hifdz al-'aql), their descendants ( hifdz an-nasl) and their wealth (hifdz mal). All of these five main objectives of sharia are intended to promote the general welfare of mankind. There are many benefits of women working and pursuing their careers. Someone who works will earn income that makes himself independent (hifdz nafs), useful and can give alms to others as recommended by his religion (hifdz ad-din). A person who does alms and good deeds will get his own honor in the eyes of his community (hifdz al 'ird). Independence and honor have noble values ​​that we can find in various verses of the Qur'an and the hadith of the Prophet Muhammad.